STUDI KOMPARASI PELAYANAN PERIZINAN TERPADU SATU PINTU (PPTSP) DALAM PENERAPAN BUDAYA ORGANISASI - Rhini Fatmasari; Eka Vidya Putra; Sri Sumiyati (Fakultas Ekonomi Universitas Negeri Jakarta, 2013)
ABSTRACTThe integrated of one-stop service is one of the major breakthroughs made by the government in order to improve public services, its specialized in the field of licensing through Permendagri number 24 concerning about Pelayanan Perizinan Terpadu Satu Pintu (PPTSP). In Government regulation district/city administration are required to have PPTSP Institutions, not only formality in the sense of institutional institutions but also in terms of value and mechanisms. General trend in Indonesia is difficult to start a formal business due to hit on the difficulty of the licenses. Although, all parties aware that businesses, especially Small and Medium Enterprises (SMEs) is one of the main pillar of the nation's economy. Overall formation of the PPTSP can be said to be successful in the district/city. But the success is not evenly distributed in the context of the development of organizational culture. If the formation of institutions PPTSP more leads to the formation of organization and mechanisms that are supported by regulatory which is the organization's culture is more directed at the behavior.The research was conducted in three PPTSP namely District Sragen, District Solok and District 50 Kota by comparing the third success and how to develop organization culture. The results showed that the success 50 Kota in develop of public service supported by the formation of organizational culture continuously. Formation of organization culture done with socializing the values espoused in organization, particularly cultural services to consumers. Success of District Sragen not be separated from the region’s ability to internalize the values of service to staff 50 Kota. The same think was not seen in District Solok and District 50 Kota. Keywords: public services, Pelayanan Perizinan Terpadu Satu Pintu (PPTSP), organizational culture, internalization of values